Abdominal aortic calcification is associated with Fibrosis‐4 index and low body mass index in type 2 diabetes patients: A retrospective cross‐sectional study. Issue 11 (23rd July 2022) - Togashi, Yu; Miyashita, Daisuke; Tsuno, Takahiro; Inoue, Ryota; Okuyama, Tomoko; Kyohara, Mayu; Nishiyama, Kuniyuki; Arai, Masanori; Kanematsu, Kenta; Kanataki, Soichiro; Terauchi, Yasuo; Shirakawa, Jun
Abstract: Aims/Introduction: This study aimed to clarify the nature of the relationship between the abdominal aortic calcification (AAC) grade and the presence of cardiovascular diseases, and determine factors related to AAC grade in people with type 2 diabetes mellitus. Materials and Methods: This retrospective cross‐sectional study enrolled 264 inpatients with type 2 diabetes mellitus. The AAC score and length were measured using the lateral abdominal radiographs. Logistic regression models were used to assess the associations between AAC scores/lengths and the presence of coronary artery disease (CAD), cerebral infarction (CI) and peripheral artery disease (PAD). The correlation between AAC scores/lengths and other clinical factors were evaluated using linear regression models. Results: The AAC score was significantly correlated with prevalent CAD and CI independent of age and smoking, but not with the prevalence of PAD. AAC length was not significantly correlated with the presence of CAD, CI or PAD; however, the sample size was insufficient to conclude, probably due to low prevalence. Both the AAC score and length were correlated inversely with body mass index (BMI) and, with the Fibrosis‐4 (Fib‐4) index >2.67; these correlations were significant after adjusting for cardiovascular risk factors and BMI, although AAC was not associated with ultrasonography‐diagnosed fatty liver. There was a significant interaction between BMI and Fib‐4 index; lower BMI and Fib‐4 index >2.67 showed a synergistic association with high AAC grade. Conclusions: AAC score is associated with CAD and CI morbidity in participants with type 2 diabetes mellitus. Low BMI and Fib‐4 index >2.67 can be valuable indicators of AAC in people with type 2 diabetes mellitus. Abstract : This cross‐sectional study assessed which factors were related to AAC in Japanese people with type 2 diabetes. We found lower BMI and Fib‐4 index >2.67 demonstrated a synergistic association with high AAC grade. Our findings suggest BMI and Fib‐4 index >2.67 as valuable indicators of AAC, and revealed an aspect of the mechanism underlying AAC development specific in individuals with type 2 diabetes.